Innovation: A comparative case study of Turkey and South Korea - Erciş, Aysel; Ünalan, Musa (My University, 2016)
When the world has been experienced the rapid technological developments, innovation have been playing a key role for countries which want to increase their economic growth and prosperity. The innovation potential of an economy influence to macroeconomic and microeconomic factors such as GDP/capita, R&D expenditures, international trade. Therefore, we want to examine the positions of innovation in Turkey and South Korea. There are some similarities in these countries to compare them in each other. In the 1980s, the per capita income in South Korea approximately equal to the per capita income in Turkey. The purpose of this paper was to examine innovation comparing Turkey and South Korea using Innovation Global Index reports between 2007 and 2015. The data source is the Global Innovation Index which is co-published by Cornell University, INSEAD, and The World Intellectual Property Organization (WIPO, an agency of the United Nations), by taking into consideration the time period 2007-2015. The results highlighted that Turkey should focus innovation more than before with regards to pillars.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Innovation; Turkey; South Korea; Global innovation index